2021
DOI: 10.1016/j.celrep.2021.109576
|View full text |Cite
|
Sign up to set email alerts
|

A histone modifier, ASXL1, interacts with NONO and is involved in paraspeckle formation in hematopoietic cells

Abstract: Paraspeckles are membraneless organelles formed through liquid-liquid phase separation and consist of multiple proteins and RNAs, including NONO, SFPQ, and NEAT1. The role of paraspeckles and the component NONO in hematopoiesis remains unknown. In this study, we show histone modifier ASXL1 is involved in paraspeckle formation. ASXL1 forms phase-separated droplets, upregulates NEAT1 expression, and increases NONO-NEAT1 interactions through the C-terminal intrinsically disordered region (IDR). In contrast, a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“… 64 Mutations in ASXL1 histone modifier have also been linked to regulation of paraspeckle formation in hematopoietic cells. 65 Current research has mainly focused on TF binding and transcription initiation and a future challenge will be to examine how the condensates are associated with transcription cycles and how they are altered in cancers. Although the functional role of nuclear condensates in cancer cells remains to be elucidated, cancer may be associated with the alteration in various other nuclear condensates.…”
Section: Alteration In Transcriptional Condensates In Cancermentioning
confidence: 99%
“… 64 Mutations in ASXL1 histone modifier have also been linked to regulation of paraspeckle formation in hematopoietic cells. 65 Current research has mainly focused on TF binding and transcription initiation and a future challenge will be to examine how the condensates are associated with transcription cycles and how they are altered in cancers. Although the functional role of nuclear condensates in cancer cells remains to be elucidated, cancer may be associated with the alteration in various other nuclear condensates.…”
Section: Alteration In Transcriptional Condensates In Cancermentioning
confidence: 99%
“…Additional sex combs‐like 1 (ASXL1) is a member of the mammalian ASXL family. ASXL1 regulates gene expression and signal transduction through interactions with multiple proteins, such as BAP1, 7 EZH2, 8 BMI1, 9 BRD4, 10 AKT, 11,12 and NONO 13 . In addition to CHIP, ASXL1 is frequently mutated in myeloid malignancies and associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…ASXL1 mutations are detected in the last exon, resulting in the translation of C‐terminally truncated ASXL1 proteins. The pathogenic ASXL1 mutants alter epigenetic modifications, 8,14–16 activate the AKT/mTOR pathway, 11 and disrupt paraspeckle formation 13 . We previously established conditional knock‐in mice carrying a C‐terminally truncated Asxl1 mutant with the floxed STOP cassette under the control of Rosa26 promoter 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it has been shown that NONO is involved not only in splicing but also in gene expression regulation, mRNA processing, gene damage response, cell proliferation, apoptosis, migration, and various other cellular functions [15,41]. Recently, it has been shown that nuclear paraspeckle formation by the histone modifier ASXL1 and the function of NONO in the nuclear paraspeckle are essential for normal differentiation from hematopoietic stem and progenitor cells (HSPCs) [42]. NONO often forms heterodimers with SFPQ (splicing factor proline/glutamine rich), another human DBHS family protein, and exerts its function [15,41].…”
Section: The Biological Importance Of the Interaction Between Rex And...mentioning
confidence: 99%